Jurnal Kata: simulated national identity and ascendant hyperrality in julian barnes's England, England - Hassan abootalebi, H., Niazi, N (Prodi Bahasa Inggris Fak sastra PETRA, 2015)
the paper sets out to analyze julian barnes novel england, england (1998) in teh light of jean baudrillards concepts of simulation and hyperreality